21st Century Agricultural Policies JC Bureau - Bureau, Jean-Christophe (2014)
IFPRI Policy Seminar "21st Century Agricultural Policies -- The 2013 EU CAP and 2014 US Farm Bill" with Jean-Christophe Bureau held 16 July 2014.